Combined acid pretreatment and co-hydrothermal carbonization to enhance energy recovery from food waste digestate. (15th August 2022) - Zhu, Xiefei; He, Mingjing; Xu, Zibo; Luo, Zejun; Gao, Bin; Ruan, Roger; Wang, Chi-Hwa; Wong, Ka-Hing; Tsang, Daniel C.W.
Graphical abstract: Highlights: A combination of acid pretreatment and co-hydrothermal process was proposed. Combination strategy significantly increased the energy potential of hydrochar. The hydrochar had a maximum HHV of 25.8 MJ kg −1 . The minimum E was 102.0 and 90.4 kJ mol −1 by FWO and KAS methods, respectively. Combustion performance of hydrochar was also improved by combination strategy. Abstract: To achieve clean and efficient utilization of food waste digestate (FWD), a novel strategy of combining acid pretreatment and co-hydrothermal carbonization was developed to prepare value-added hydrochar from food waste digestate. The acid pretreatment of FWD was carried out with 1 M HCl for 8 h at a solid-to-liquid ratio of 1:5. In addition to the characterization of physicochemical properties including proximate analysis, elemental content, heating value, and thermal stability of the hydrochar, TG-FTIR-MS and TG-DSC were used to evaluate the pyrolysis gaseous products and combustion performance of hydrochar. The results showed that the combination strategy enhanced the fuel properties of the hydrochar. In particular, the ash content of hydrochar was reduced to a minimum of 6.3%, thereby increasing the heating value by nearly two folds. The acid pretreatment and the addition of wood waste increased the H/C and O/C ratios of hydrochar while enhancing the thermal stability of hydrochar. The peak types of the infrared spectrum and mass spectrum of the pyrolysis gaseous products remained largely unchanged. Based on the comprehensive combustion index and combustion stability index, blending with wood waste could obtain a comparable combustion performance of the hydrochar with multiple cycles of acid pretreatment. The apparent activation energy of hydrochar was 102.0 and 90.4 kJ mol −1 by FWO and KAS methods, respectively. The strategy advocated here presents a new 'green' perspective for the large-scale energy recovery from food waste digestate that is currently under-utilized.